THE PROGRAM OF SOCIOLOGICAL RESEARCH AS A GUARANTEE OF RESEARCH EFFECTIVENESS - Khachatryan, Artak (Journal of Sociology: Bulletin of Yerevan University, 2019)
This article discusses some issues related to the program of sociological research, in particular, the requirements for defining the research problem and object. Referring to Soviet and post-Soviet Russian-language literature on sociological research, the author attempts to revise their definitions. The article expresses the idea that the object of sociological research is ultimately people because, without their social participation, no social phenomenon is manifested. The research problem is the question that the researcher raises when getting acquainted with a problematic situation. The author implies that the research problem carries a social contradiction. He develops the idea that the contradiction arises in the researcher's consciousness when he combines the problematic situation with his perceptions of the subject. It is then that a contradiction arises between his expectations and reality. The basis of sociological research is usually not a social problem, as many authors point out, but a research and scientific problem.
Keywords: program of sociological research, problem situation, research problem, research object, definition of main terms, hypothesis